2017
DOI: 10.1080/14767058.2016.1275546
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between first trimester aneuploidy screening test serum analytes and placenta accreta

Abstract: Higher first trimester serum PAPP-A and fβhCG MoM values seem to be associated with placenta accreta in women with placenta previa. Further studies are needed to use these promising additional tools for early detection of placenta accreta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…Their group also demonstrated an increased risk of abnormal karyotype in pregnancies with both abnormally high (>5.0 MoM) and low (<0.2 MoM) levels of free β‐hCG. In addition to being associated with fetal aneuploidy, abnormal levels of these maternal serum analytes have been associated with an increased risk of several placental‐related obstetrical complications such as intrauterine growth restriction (IUGR), preeclampsia, placental abruption, morbidly adherent placenta, and preterm birth . Krantz et al have reported that abnormally low (<0.21 MoM) levels of free β‐hCG is associated with increased risk of fetal growth restriction (OR 2.7, 95% CI, 1.3‐5.9).…”
Section: Discussionmentioning
confidence: 99%
“…Their group also demonstrated an increased risk of abnormal karyotype in pregnancies with both abnormally high (>5.0 MoM) and low (<0.2 MoM) levels of free β‐hCG. In addition to being associated with fetal aneuploidy, abnormal levels of these maternal serum analytes have been associated with an increased risk of several placental‐related obstetrical complications such as intrauterine growth restriction (IUGR), preeclampsia, placental abruption, morbidly adherent placenta, and preterm birth . Krantz et al have reported that abnormally low (<0.21 MoM) levels of free β‐hCG is associated with increased risk of fetal growth restriction (OR 2.7, 95% CI, 1.3‐5.9).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in a larger retrospective case-control study, Dreux et al compiled a database consisting of 69 PAS patients who underwent routine second trimester maternal aneuploidy screening. The control group consisted of 552 serum samples (1 : 8 ratio) matched by maternal age, randomly selected from the routine second trimester maternal serum screening databases [ 81 ]. Second trimester free β -hCG was significantly higher, 1.50 MoM versus 1 MoM ( P < 0.0001), in cases of clinically suspected and/or histologically confirmed cases of PAS ( P < 0.0001) versus the control group.…”
Section: Biomarkersmentioning
confidence: 99%
“…En la placenta mórbidamente adherida se presenta una excesiva invasión del trofoblasto en el miometrio debido a una deficiente decidualizacion 9 . Adicionalmente la placenta mórbidamente adherida se ha asociado con morbimortalidad neonatal y fetal; donde las causas identificadas se relacionan con ruptura prematura de membranas 16 , anomalías congénitas 16,17 , hemorragia anteparto e infección, que pueden conducir a prematuridad extrema, lesiones neurológicas, gastrointestinales o cardiorrespiratorias 16 .…”
Section: Discussionunclassified
“…La trisomía 13, es una alteración cromosómica, con una incidencia de uno de cada 12.000 nacidos vivos y se considera la tercera trisomía más común 13 se debe a una no-disyunción cromosómica durante la meiosis, principalmente en el gameto materno; El fenotipo se caracterizan por presentar lesiones en sistema nervioso central (holoprosencefalia, malformación de Dandy-Walker, microcefalia, mielomenigocele), labio-paladar hendido, aplasia cutis, microftalmia, higroma quístico, cardiopatía congénita, onfalocele, anormalidades urogenitales, polidactilia postaxial, calcáneo prominente y uñas hiperconvexas 14 . Desde los años 90 se ha utilizado durante el primer trimestre la combinación de factores clínicos (edad materna), ecográficos (translucencia nucal) y marcadores bioquímicos como la proteína A del plasma sanguíneo asociada al embarazo (PAPP-A) y la fracción libre de la gonadotrofina coriónica humana (fβhCG) como pruebas para el diagnóstico de aneuploidías con sensibilidad del 85-90% y falsos positivos (FP) del 5%, algunos estudios han demostrados que la placenta previa acompañada de acretismo pueden corresponder a algunos de estos casos de FP sin que se halla descrito en la literatura la presencia de estos dos hallazgos de manera concomitante 9 . Este es un reporte de caso de una gestante con placenta percreta y producto con trisomía 13, quien refiere deseo de interrupción voluntaria del embarazo, amparado en la legislación colombiana (sentencia C-355 del 2006) 15 .…”
Section: Introductionunclassified